Performance indicators and success factors of the South African men's rugby sevens team during the 2017/2018 World Rugby Sevens Series - Opperman, E. (University of Stellenbosch, 2020)
Background: Rugby sevens consists of a complex interaction of various actions and events. For trainers to distinguish between events that are more likely to lead to a successful match outcome is a difficult task. Success factors are Performance Indicators (PIs) that were significantly prominent during matches won when compared to matches lost and most likely contributed to a successful match outcome. Aim: The aim of this study was to determine the PIs that significantly related to successful match outcome during the 2017/2018 World Rugby Sevens Series of the Blitsboks. Methods: Broadcasted video footage of 59 matches played by the South African men`s rugby sevens team during the 2017/2018 World Rugby Sevens Series were analysed using rugby video analysing software (Stratus V3.6.3, Mobii, South Africa). Matches were divided into two categories; matches won versus matches lost. One-way ANOVA was used to test for significant differences in PIs between the groups. Results: Success factors were displayed for the higher number of successful tackles made (p = 0.03) and fewer tackles missed (p = <0.01) as well as a higher number of restart kicks (p <0.01) during matches won. Success factors for the breakdown included more turnovers won (p = 0.05), fewer rucks retained by infringement (p = 0.04), more defensive breakdowns formed (p < 0.01) as well as committing one player to defensive breakdowns (p = 0.02). During matches won, significantly fewer breakdowns were formed in zone B and zone D. Conclusion: During the 2017/2018 World Rugby Sevens Series, it was shown the most successful team relied on a strong effective tackling ability. To attack successfully, teams need to seek turnovers by optimally committing players to the contest without sacrificing defence, adopt aggressive risk-reward tactics and play in the correct areas of the field (zone A and zone C) to be in control of the territory.